RNA Sequencing Analysis Reveals Interactions between Breast Cancer or Melanoma Cells and the Tissue Microenvironment during Brain Metastasis. (22nd January 2017) - Sato, Ryo; Nakano, Teppei; Hosonaga, Mari; Sampetrean, Oltea; Harigai, Ritsuko; Sasaki, Takashi; Koya, Ikuko; Okano, Hideyuki; Kudoh, Jun; Saya, Hideyuki; Arima, Yoshimi
Abstract : Metastasis is the main cause of treatment failure and death in cancer patients. Metastasis of tumor cells to the brain occurs frequently in individuals with breast cancer, non–small cell lung cancer, or melanoma. Despite recent advances in our understanding of the causes and in the treatment of primary tumors, the biological and molecular mechanisms underlying the metastasis of cancer cells to the brain have remained unclear. Metastasizing cancer cells interact with their microenvironment in the brain to establish metastases. We have now developed mouse models of brain metastasis based on intracardiac injection of human breast cancer or melanoma cell lines, and we have performed RNA sequencing analysis to identify genes in mouse brain tissue and the human cancer cells whose expression is associated specifically with metastasis. We found that the expressions of the mouse genes Tph2, Sspo, Ptprq, and Pole as well as those of the human genes CXCR4, PLLP, TNFSF4, VCAM1, SLC8A2, and SLC7A11 were upregulated in brain tissue harboring metastases. Further characterization of such genes that contribute to the establishment of brain metastases may provide a basis for the development of new therapeutic strategies and consequent improvement in the prognosis of cancer patients.